2021
DOI: 10.1136/bmjopen-2020-047028
|View full text |Cite
|
Sign up to set email alerts
|

Opioid maintenance treatment in the Czech Republic, Norway and Denmark: a study protocol of a comparative registry linkage study

Abstract: IntroductionOpioid maintenance treatment (OMT) varies across settings and between countries. We plan to use data from several nationwide health and population registers to further improve the knowledge base established from earlier studies. Our aim is to study OMT adherence trajectories and to identify factors associated with improved outcomes for OMT patients across the Czech Republic, Norway and Denmark, in order to further improve OMT and our understanding of the key elements of treatment success.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This was a registry-linkage study on the national samples of OAT patients from Czechia and Norway in 2010-2019. The protocols for the overall comparative registry linkage studies [32,33] and previous findings on somatic comorbidity and mortality in the same cohort of OAT patients can be found elsewhere [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…This was a registry-linkage study on the national samples of OAT patients from Czechia and Norway in 2010-2019. The protocols for the overall comparative registry linkage studies [32,33] and previous findings on somatic comorbidity and mortality in the same cohort of OAT patients can be found elsewhere [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…In each country, physicians are legally required to report data to these registries. The protocol for the overall comparative registry linkage study can be found elsewhere [[24]]. All three cohorts have been analysed separately.…”
Section: Methodsmentioning
confidence: 99%
“…We used a prospective cohort approach linking the data sources by using the unique civil registration number assigned to all residents in both countries ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nation-wide OMT registers with detailed information on an individual level about time of enrolment in treatment, discontinuation, re-entry, and termination of OMT medication exist in Czechia and Denmark ( 21 ), and may be linked to information on time of death and causes of death obtained from nation-wide mortality registries. Furthermore, these two countries represent distinct treatment settings.…”
Section: Introductionmentioning
confidence: 99%